The influencing factors on choice behavior regarding green electronic products: Based on the green perceived value model - Muhammad Danish; Saqib Ali; Muhammad Azeem Ahmad; Hasan Zahid (Economies, 2019)
Electronic/electrical waste (e-waste) has now become a global concern due to its negative impact on the environment and health. This negative effect of e-waste is increasing with the advancement in the electronics industry, especially in Pakistan, which is the leading e-waste disposal destination. Therefore, this study aims to find consumer choice behavior regarding green electronics in Pakistan. For this purpose, a multidimensional modified green perceived model (functional value quality, functional value price, social value identity, social value responsibility, emotional value, and conditional value) is used. Cross-sectional data is collected from 237 consumers through a self-administrative questionnaire. The results of variance-based structural equation modeling (SEM) (partial least squares (PLS)-SEM) suggested that functional value price, quality, social value identity, responsibility, emotional value, and conditional value positively and significantly influence the consumer choice behavior regarding green electronics. the possible reasons for the findings and the implications for managers and policymakers are discussed. Limitations of the study and future research directions are also suggested.
Keywords: 330; e-waste; green electronics; green perceived value model; Pakistan